PENGARUH INTERNALISASI NILAI QANA'AH TERHADAP GAYA HIDUP HEDONISME SISWA MAN 1 BANJARNEGARA - Luthfiah Tri Yunita; Naufal Zuhdi 'Afif (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This research is motivated by the increasing tendency towards a hedonistic lifestyle among adolescents, influenced by the development of social media, social environments, and consumer culture. One Islamic value that can control hedonistic behavior is the value of contentment (qana'ah). Therefore, this study aims to determine the relationship between the internalization of the value of contentment and the hedonistic lifestyle of students at MAN 1 Banjarnegara. This research used a quantitative approach with a correlational approach. The population in this study consisted of 30 students, and the entire population was used as the sample using a total sampling technique. Data collection was conducted through questionnaires and observations. The research instrument used a Likert scale, whose validity and reliability were tested using SPSS. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and the Spearman Rank correlation test (Spearman's Rho). The results showed that the internalization of the value of contentment obtained a mean score of 30.47, while the hedonistic lifestyle variable obtained a mean score of 27.17. The results of the normality test indicated that the data were not normally distributed, so the Spearman Rank correlation test was used to test the hypothesis. The correlation test yielded a significance value of 0.000 < 0.05, with a correlation coefficient of 0.871, indicating a significant, but very strong, relationship between the internalization of contentment values and the hedonistic lifestyle of students at MAN 1 Banjarnegara. The results showed that the higher the internalization of contentment values in students, the lower their tendency toward a hedonistic lifestyle.